A STUDY OF THE COMPONENTS OF ETHICAL LEADERSHIP OF SCHOOL ADMINISTRATORS - Chantawong, Jarunee; Pheasa, Akkaluck; Satiennopakao , Pornthep (Journal of MCU Nakhondhat, 2024)
The purpose of this research paper is to study the ethical leadership elements of school administrators as a quantitative research with two steps: 1) Synthesis of ethical leadership elements of school administrators by studying from relevant documents and research; 2) Evaluation of the appropriateness of the ethical leadership elements of school administrators by qualified persons. There are 5 people, including higher education teachers, school administrators, and teachers. The tools used in the research include document synthesis and a 5-level estimation scale questionnaire. The statistics used in the research include frequency, percentage, mean, and standard deviation. The results showed that the elements of ethical leadership of school administrators consisted of 6 elements and 30 indicators, including 1) Fairness 5 indicators, 2) Integrity 5 indicators, 3) Trust 5 indicators, 4) Responsibility 5 indicators, 5) Respectability 5 indicators, and 6) Good citizenship 5 indicators. Elements of Ethical Leadership of School Administrators All elements are suitable in the overall category at the greatest level. When considered individually, all aspects are at the highest level, sorted by the average in descending order. 1) Responsibility, 2) Good Citizenship, 3) Justice, 4) Respectability, 5) Honesty, and 6) Trust, respectively. Therefore, administrators should use these elements as a guide to develop the training of school administrators to have such ethical leadership.